Chronic kidney dissease and complex urinary tract infection in children with left renal agenesis : A case report - Maria Ulfa; Tunjung Wibowo; Desy Rusmawatiningtyas; Kristia Hermawan (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2021)
Child with left renal agenesis fulfill the diagnostic criteria for chronic kidney disease due to its structural abnormalities that lasted for more than three months. It is important to monitored the disease progression and also growth, development and quality of life in children with chronic disease. Management of other risk factors that can accelerate disease progression must be carried out comprehensively. The patient's was 9 months old girl with stage I chronic kidney disease and also having recurrent complex urinary tract infections with left renal agenesis. The interventions was  to identify other abnormalities of the urinary tract and syndromic disorders, prevention of urinary tract infection (UTI) recurrence, prevention of renal injury, renal scaring and dietary education. After 18 months of observation there was no urinary tract abnormality in imaging results, there was one episode of mild  recurrent UTI, no renal injury and there was no sign of renal scaring. The final outcome was no significant decrease in glomerular filtration rate (GFR), growth and development was good and good quality of life. The immunizations was given as scheduled. Monitoring and multidisciplinary intervention of prognostic variables such as urinary tract and syndromic disorders, recurrence UTI, renal injury, renal scaring and diet in children with chronic kidney disease are important for optimal outcome. No decrease of GFR, good growth, development and optimal quality of life and also knowing the progression of  chronic kidney disease was the final outcomes of the intervention.